Efek intervensi minuman tempe terhadap tekanan darah penderita hipertensi dan hiperkolesterolemia - Ansarullah, Alfia; hardinsyah, Hardinsyah; Marliyati, Sri Anna; Astawan, Made (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The aim of this study was to determine the effect of tempe drink intervention on blood pressure of hypertension and also hypercholesterolemia subjects. This study used a Randomized Controlled Trial (RCT) design with 30 males and females subjects, who were divided into three treatment groups-tempe drink of A formulated from local sprouted soybean (TDA), tempe drink of B formulated from imported soybean (TDB), and control. The inclusion criterias were adults aged 25-55 years, not being menopause and pregnant, total cholesterol levels ≥200 mg/dl, systolic blood pressure level 121-139 mmHg, diastolic blood pressure level 81-89 mmHg and willing to partcipate in research by signing an informed consent. The tempe drink was given three glasses a day for four weeks continuously, contained at least 25 g of protein/day. The control group was not given the tempe drink. Blood pressure data were collected every week during intervention. The results showed that the effect of TDA and TDB compared to control subjects on systolic blood pressure was significantly different. Other ways the effect of TDA and TDB compared to control subjects on diastolic blood pressure was not significantly different, but the trend was decreasing.